Role of Phytochemicals in Skin Photoprotection via Regulation of Nrf2 - Chaiprasongsuk, Anyamanee; Panich, Uraiwan (Frontiers in Pharmacology, 2022)
Ethnopharmacological studies have become increasingly valuable in the development of botanical products and their bioactive phytochemicals as novel and effective preventive and therapeutic strategies for various diseases including skin photoaging and photodamage-related skin problems including abnormal pigmentation and inflammation. Exploring the roles of phytochemicals in mitigating ultraviolet radiation (UVR)-induced skin damage is thus of importance to offer insights into medicinal and ethnopharmacological potential for development of novel and effective photoprotective agents. UVR plays a role in the skin premature aging (or photoaging) or impaired skin integrity and function through triggering various biological responses of skin cells including apoptosis, oxidative stress, DNA damage and inflammation. In addition, melanin produced by epidermal melanocytes play a protective role against UVR-induced skin damage and therefore hyperpigmentation mediated by UV irradiation could reflect a sign of defensive response of the skin to stress. However, alteration in melanin synthesis may be implicated in skin damage, particularly in individuals with fair skin. Oxidative stress induced by UVR contributes to the process of skin aging and inflammation through the activation of related signaling pathways such as the mitogen-activated protein kinase (MAPK)/activator protein-1 (AP-1), the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt), the nuclear factor kappa B (NF-B) and the signal transducer and activator of transcription (STAT) in epidermal keratinocytes and dermal fibroblasts. ROS formation induced by UVR also plays a role in regulation of melanogenesis in melanocytes via modulating MAPK, PI3K/Akt and the melanocortin 1 receptor (MC1R)-microphthalmia-associated transcription factor (MITF) signaling cascades. Additionally, nuclear factor erythroid 2-related factor 2 (Nrf2)-regulated antioxidant defenses can affect the major signaling pathways involved in regulation of photoaging, inflammation associated with a compromised skin barrier and melanogenesis. This review thus highlights the roles of phytochemicals potentially acting as Nrf2 inducers in improving photoaging, skin barrier impairment and hyperpigmentation via regulation of cellular homeostasis involved in skin integrity and function. Taken together, understanding the role of phytochemicals targeting Nrf2 in photoprotection could provide an insight into potential development of natural products as a promising strategy to delay skin photoaging and improve skin conditions.